2018
DOI: 10.1177/0963689718780309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mesenchymal Stromal Cells Isolated from Murine Adipose Tissue and Bone Marrow in the Treatment of Spinal Cord Injury

Abstract: The use of mesenchymal stromal cell (MSC) transplantation to repair the injured spinal cord has shown consistent benefits in preclinical models. However, the low survival rate of grafted MSC is one of the most important problems. In the injured spinal cord, transplanted cells are exposed to hypoxic conditions and exposed to nutritional deficiency caused by poor vascular supply. Also, the transplanted MSCs face cytotoxic stressors that cause cell death. The aim of this study was to compare adipose-derived MSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 56 publications
0
41
0
Order By: Relevance
“…What mediates the greater therapeutic effect of AD-MSCs in SCI compared to BM-MSCs or DP-MSCs remains to be fully understood. However, biological advantages in the proliferative capacity, cell viability under oxidative stress, secreted proteins, and immunomodulatory effects have been previously discussed for AD-MSCs and may be critical factors [23,76]. These data indicate that application of MSCs combined with fibrin matrix into the surface of spinal cord may be an effective and safe approach for delivering cells to the damaged area.…”
Section: Discussionmentioning
confidence: 94%
“…What mediates the greater therapeutic effect of AD-MSCs in SCI compared to BM-MSCs or DP-MSCs remains to be fully understood. However, biological advantages in the proliferative capacity, cell viability under oxidative stress, secreted proteins, and immunomodulatory effects have been previously discussed for AD-MSCs and may be critical factors [23,76]. These data indicate that application of MSCs combined with fibrin matrix into the surface of spinal cord may be an effective and safe approach for delivering cells to the damaged area.…”
Section: Discussionmentioning
confidence: 94%
“…Herein, bone marrow mesenchymal stem cells have been commonly considered as the first source of MSCs for SCI treatment. However, in the last years, several studies in animal models of SCI have demonstrated comparable results with AMSCs (Im, ; Kolar, Kingham, Novikova, Wiberg, & Novikov, ; Takahashi et al, ; Z. Zhou et al, ) which otherwise are much easier to isolate from healthy donors and in larger amounts than from bone marrow (Strioga, Viswanahatan, Darinskas, Slaby, & Michalek, ). These properties make of them a very attractive cell therapy alternative for SCI, as highlights the four clinical trials using these cells in subacute or chronic stages after SCI currently underway (Bajek et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Among cell therapies, mesenchymal stem cell (MSC) transplantation is an attractive and promising approach for treating SCI favoured by its excellent safety profile and efficacy potential, as extensively reported in preclinical models and clinical trials of acute, subacute, and chronic SCI (Dasari, Veeravalli, & Dinh, ; Qu & Zhang, ; Shende & Subedi, ; Vawda & Fehlings, ). In particular, adipose MSCs (AMSCs) are easily obtained and have excellent expansion capacities, as well as a unique immunomodulatory and paracrine competence able to modulate many of the detrimental effects elicited after acute SCI (Mazini, Rochette, Amine, & Malka, ; Menezes et al, ; Takahashi et al, ). These effects together with a proven preclinical efficacy and safety profile have paved the way for the clinical assessment of AMSCs in a variety of trials (Bajek et al, ; Hur et al, ; Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of grafted MSCs may not survive the first few days posttransplantation 22 . Thus, decreasing the expression of inflammation mediators may enhance MSC survival and improve their therapeutic efficacy 23,24 . In our study, LPS and FK506 were used to modulate the local immune microenvironment in neurotmesis.…”
Section: Discussionmentioning
confidence: 98%
“…MSCs can promote nerve regeneration after transplantation 1,18–20 . Unfortunately, the survival of transplanted MSCs is jeopardized by the unfavorable immune microenvironment of injured nerves, which substantially hampers the beneficial effect of MSCs on nerve repair 21–24 . It has been reported that the survival rate of MSCs can be increased by FK506 after spinal cord injury 14 .…”
Section: Introductionmentioning
confidence: 99%